Gel polymer electrolytes for lithium ion batteries: Fabrication, characterization and performance - Liang, Shishuo; Yan, Wenqi; Wu, Xu; Zhang, Yi; Zhu, Yusong; Wang, Hongwei; Wu, Yuping (Solid state ionics, 2018)
Gel polymer electrolytes (GPEs) with characteristics of both solid and liquid electrolytes have received increasing attentions. Several polymer matrices have been employed as hosts for GPEs in order to investigate their possible applications in lithium ion batteries (LIBs). Herein, we review some crucial physico-chemical and electrochemical properties of GPEs for LIBs as well as the characterization techniques for their evaluation. Then, the different preparation and modification methods of GPEs are summarized. Meanwhile, the effects of preparation on the performance of electrolytes are discussed. Finally, future directions of GPEs are pointed out. [Display omitted] •Some crucial properties of GPEs for LIBs are discussed.•Characterization techniques for crucial properties of GPEs are presented.•Different preparation and modification methods of GPEs are summarized.•The effects of preparation on the performances of electrolytes are also discussed.•Future research developments of GPEs for LIBs are pointed out.